Penerapan Bimbingan Kelompok Dengan Metode Kisah Dalam Membantu Perencanaan Karir - Fitri Kurniati; Abdur Razzaq; Lena Marianti (Journal of Society Counseling, 2023)
This study is entitled "Implementation of Group Guidance with the Story Method to Assist Career Planning for Beneficiaries of the Budi Perkasa Sentra Palembang". Career planning is a process that goes through individual employees to identify and take steps to achieve their career goals. This study aims to find out the description of career planning for the beneficiaries of the Budi Perkasa Sentra Palembang and to find out the application of group guidance with the story method in assisting career planning for the beneficiaries of the Sentra Budi Perkasa Palembang. This research is a field research using a qualitative approach. The subjects in this study were six beneficiaries of Sentra Budi Perkasa Palembang. Data collection techniques are observation, interviews, and documentation. Data analysis techniques use the Miles and Huberman models, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that prior to implementing group guidance services using the story method to assist career planning for beneficiaries of the Budi Perkasa Sentra Palembang there were still many beneficiaries who had unclear future careers as indicated by knowledge and attitude aspects. Furthermore, after implementing group guidance services with the story method to assist career planning for beneficiaries of the Budi Perkasa Palembang Center, beneficiaries have started to have thoughts about future career plans after leaving the Budi Perkasa Palembang Sentra program. Thus the application of group guidance with the story method for career planning for beneficiaries at the Budi Perkasa Sentra Palembang has a significant effect.